SISTEM INFORMASI MANAJEMEN GUDANG PERKEBUNAN KELAPA SAWIT DENGAN PENDEKATAN HYBRID MENINGKATKAN EFISIENSI DAN AKURASI INVENTORI - Ready Perdana; Ratu Mutiara Siregar; Andi Prayogi (LPPM Universitas Abdurrab, 2026)
Warehouse management in oil palm plantations still faces challenges including manual recording that is prone to errors, inventory data discrepancies, and limited internet connectivity in remote areas. This study aims to design and develop a Warehouse Management Information System using a hybrid approach that supports offline and online operations, implement a data synchronization mechanism between local storage and the main database, and improve operational efficiency and inventory accuracy in oil palm plantation environments. The Research and Development (R&D) method with a Prototype approach was employed. The system was developed using Flutter as the frontend framework, Laravel as the backend and API, SQLite as the local device database, and MySQL as the main server database. Testing was conducted using the Blackbox Testing method with 46 test scenarios covering eight functional modules. The results show a 100% success rate across all functional test scenarios. The system operates in hybrid mode, automatically synchronizes data via a push-pull mechanism using UUID as an idempotency key, and provides inventory management features including item master data, goods receipt, goods issuance, stock opname, multi-level approval, digital reporting (PDF and Excel), and activity logs. The system has been proven to improve operational efficiency by eliminating redundant recording processes and enabling remote digital approvals, and to enhance inventory accuracy through automatic input validation, duplicate data prevention, and a structured audit trail.